2004
DOI: 10.1213/01.ane.0000112306.71113.5e
|View full text |Cite
|
Sign up to set email alerts
|

The Failure of Retrograde Autologous Priming of the Cardiopulmonary Bypass Circuit to Reduce Blood Use After Cardiac Surgical Procedures

Abstract: Priming of the cardiopulmonary bypass circuit with the patients' own blood (retrograde autologous priming) resulted in insignificant reductions in blood use in a large, unselected group of patients undergoing cardiac surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 11 publications
8
33
1
2
Order By: Relevance
“…That study concluded that there was no clinical effectiveness in the use of RAP. 12 Our study showed that there was a significant difference in pump priming volumes, which is to be expected when comparing a RAP with a non-RAP procedure, but there was no difference in transfusion rate between RAP and non-RAP patients. Interestingly, there was a significant difference in the on-CPB Hb levels (RAP 9.1g/dl vs non-RAP 7.7g/dl, p<0.001), which may confer an advantage in postoperative recovery to the RAP group.…”
Section: Discussionsupporting
confidence: 50%
“…That study concluded that there was no clinical effectiveness in the use of RAP. 12 Our study showed that there was a significant difference in pump priming volumes, which is to be expected when comparing a RAP with a non-RAP procedure, but there was no difference in transfusion rate between RAP and non-RAP patients. Interestingly, there was a significant difference in the on-CPB Hb levels (RAP 9.1g/dl vs non-RAP 7.7g/dl, p<0.001), which may confer an advantage in postoperative recovery to the RAP group.…”
Section: Discussionsupporting
confidence: 50%
“…Although recent isolated studies confirm the benefits of recent RAP [13], at least two studies in meta-analysis are not favorable [14,15]. These results suggest that overall.…”
Section: Discussionmentioning
confidence: 81%
“…The efficacy of RAP in adult patients is still controversial and has not yet been reported in children. 19,20 …”
Section: Retrograde Autologous Blood Priming (Rap)mentioning
confidence: 99%